Botulinum Toxin Type A Reconstituted with Lidocaine: A Report of 1000 Consecutive Cases - Pierfrancesco Bove; Vincenzo Santillo; Giuseppe Colella; Rita Vitagliano; Romolo Fragola; Giorgio Lo Giudice; Nicola Zerbinati; Ivo Ferrieri; Raffaele Rauso (Applied Sciences, 2021)
(1) Background: There is an increasing demand for a reversal of the aging process and, nowadays, more patients are seeking minimally invasive methods instead of surgery to meet this goal. The purpose of this paper is to evaluate the predictability of the off-label aesthetic use of botulinum toxin type A (BoNTA) reconstituted with lidocaine. (2) Methods: One thousand treatments, between January 2010 and January 2020, with BoNTA reconstituted with lidocaine for the rejuvenation of the upper third of the face, were performed and retrospectively evaluated. (3) Results: A few seconds after the BoNTA injections, the effect of muscle paralysis was seen in all cases; this allowed providing an optimal symmetric result with no need for a touch-up procedure at the control after three weeks. A burning sensation during the injections was claimed by almost all patients. Major complications were not registered. No touch-up procedures were required. (4) Conclusions: The results of this study show how the reconstitution of BoNTA with lidocaine may avoid imperfect results after the injections; the immediate feedback on the extent of paralysis to be expected from the chemodenervation action of BoNTA allows the physician to have immediate control of the final result.